International application of standards for health care quality, access and evaluation of services for early intervention in psychotic disorders. Issue 3 (25th May 2020) - Addington, Donald; Cheng, Chiachen Cheng; French, Paul; Killackey, Eoin; Melau, Marianne; Meneghelli, Anna; Nordentoft, Merete; Nossel, Ilana; Preti, Antonio; Smith, Jo
Abstract: Aim: Standards for health care quality, access and evaluation of early intervention in psychosis services are required to assess implementation, provide accountability to service users and funders and support quality assurance. The aim of this article is to review the application of standards in Europe and North America. Methods: Descriptive methods will be used to illustrate the organizational context in which standards are being applied and used, specific measures being applied and results so far. Results: Both fidelity scales and quality indicators of health care are being used. Fidelity scales are being applied in Australia, Canada, Denmark, Italy and United States. In England, quality indicators derived from the National Institute for Health and Care Excellence guidance are being used. Conclusion: In the last 4 years, significant progress has been made in the development and application of measures that assess quality and access to evidence‐based practices for early intervention in psychosis services. This represents an important step towards providing accountability, improving outcomes and service user experience. The methods used allow for comparison between the services that are assessed with the same methods, but there is a need to compare the different methods. Further research is also required to explore links between quality of care and outcomes for community mental health services that deliver early intervention in psychotic disorders.